The Role of Krüppel-like Factor 4 in Renal Fibrosis - Ke, Ben; Zhang, Afei; Wu, Xianfeng; Fang, Xiangdong (Frontiers in Physiology, 2015)
Abstract Chronic kidney disease (CKD) caused by renal fibrosis is an important public health concern. It is therefore necessary to understand the molecular pathogenesis of renal fibrosis in order to develop novel therapeutic strategies. KLF4 is the most extensively studied factor among the various members of the Krüppel-like factor (KLF) family of zinc finger-containing transcription factors. Many studies have demonstrated that KLF4 inhibits the activation of myofibroblasts and exerts an inhibitory effect on fibrosis. However, other studies have indicated that KLF4 may promote renal fibrosis. These controversial results suggest that KLF4 may be crucially involved in the development of renal fibrosis, although the underlying mechanism(s) remain unclear. Here, we summarize the recent progress made in understanding the role of KLF4 in renal fibrosis. Together, these findings suggest that KLF4 may participate in the development of renal fibrosis, but that its inhibition of fibrosis is greater than its promotion of the condition, which suggests that KLF4 may serve as a novel therapeutic target for renal fibrosis.